Effective methods of teaching the image of a teacher in Kazakh prose - Ospanova, G.T.; Kulmanov, K.S.; Askarova, A.Sh. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
The article considers new methods of teaching the image of a teacher in Kazakh prose. The place of a teacher in the upbringing of youth and generations through literary works and the consideration of his artistic depiction in Kazakh prose will enrich the topic. Analyzing the essence and content of teaching the great personality of a teacher who educates the young generation through literary works, a comprehensive analysis of the definitions of the concept is made. The purpose of the study is to identify effective ways of educating students through works that define the image of a teacher. Focusing on the concepts of ‘teacher’ and ‘tutor’ in the Kazakh worldview, the difference between their role in modern society and their role in literary works is distinguished. The novelty of the study is that the thematic ideas and searches of Kazakh writers in the creation of the image of a teacher in the methodology of teaching the Kazakh language were analyzed, and effective teaching methods were considered. The study was the first to examine and analyze the methodology for studying the image of a teacher in Kazakh prose, its spiritual, ethical and aesthetic nature. The results of the study have the potential to be used in the methodology of teaching literature and the Kazakh language, in the field of aesthetic education of students in the field of combining language and education.